Radiation measurement of boron neutron capture therapy research facility at T riga Mark-II research reactor Malaysia - Safwan, Shalbi; Norazlianie, Sazali; Muhammad Aliff Ashraff, Rosdi; Faridah Mohamad, Idris (IOP Conf. Series: Materials Science and Engineering, 2021)
Proper shielding ionizing radiations is a mandatory requirement in all nuclear facilities owing to the harmful effects of radiation on workers and general public. The present work is aimed to measure neutron fluxes and gamma fluxes around the Boron Neutron Capture Therapy (BNCT) research facility at the PUSPATI TRIGA Reactor. This measurement is needed in the subsequent safety assessment so as to ensure the research facility is safely operated